Authenticity as a value co-creator of tourism experiences - Ramkissoon, Haywantee; Uysal, M. (CABI, 2014)
This book attempts to outline value creation in tourist experiences, theoretically and practically, in order to obtain new understandings and models to help identify how value creation is changing within the tourism industry and demonstrate ways in which both tourists and settings can proactively take part in this change, thus becoming a vital element in its success. By including two major aspects of value creation, i.e., psychological and physiological aspects of a tourist journey, the book puts forward fundamental ideas on how to acknowledge and handle tourist experience as a value-based construct and personal narratives. The book has 19 chapters and a subject index.